Migration, education and change - Luchtenberg, Sigrid, 1946- (London ; New York : Routledge, 2004)
This book discusses the impact of different forms of migration on education in Europe and Australia. It considers issues such as identity, citizenship and language education.
Introduction / Sigrid Luchtenberg -- Transnationalism and migration : new challenges for the social sciences and education / Ludger Pries -- (New forms of) migration : challenges for education / Sigrid Luchtenberg -- Collective solidarity and the construction of social identities in school : a case study on immigrant youths in post-unification West Berlin / Sabine Mannitz -- The education of migrants and minorities in Britain / Sally Tomlinson -- Discovering the ethnicized school : the case of France / Françoise Lorcerie -- New migration in Europe : educational changes and challenges, a perspective from Greece / Soula Mitakidou and Giorgos Tsiakalos -- European perspectives on immigrant minority languages at home and at school / Guus Extra and Kutlay Yağmur -- Sweden as a multilingual and multicultural nation : effects on school and education / Tore Otterup -- Australia : educational changes and challenges in response to multiculturalism, globalization and transnationalism / Christine Inglis.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Immigrants -- Education; Multicultural education; Emigration and immigration -- Social aspects; Éducation interculturelle; Émigration et immigration -- Aspect social; EDUCATION -- Special Education -- Learning Disabilities; Emigration and immigration -- Social aspects; Immigrants -- Education; Multicultural education; Multiculturele samenlevingen; Scholing; Interkulturell pedagogik; Mångfald i skolan; Invandrarundervisning; Invandrarelever; Invandrarbarn -- utbildning och undervisning